Psychosocial health disparities in early childhood: Socioeconomic status and parent migration background - Jie Luo; Amy van Grieken; Junwen Yang-Huang; Suzanne J. van den Toren; Hein Raat (Elsevier, 2022)
The association between low socioeconomic status (SES), migration background and psychosocial health could be various in different age stages, rare research has investigated associations in very early childhood. Cross-sectional data of SES, parental migration background, and child's psychosocial problems among 2149 children were collected (Mage = 24.6 ± 1.8 months, 49.9% girls) from a community population. Indicators of SES included parental education level, maternal work status, and family composition. Child's psychosocial problems, including social-emotional problems and delay in social-emotional competence, were assessed by the Brief Infant-Toddler Social and Emotional Assessment Problem scale and Competence scale, respectively. Interaction effects between SES and maternal migration background in risk of psychosocial problems were found. Among children of a native-born mother, lower maternal and paternal education levels indicated a higher risk of social-emotional problems and competence delay, respectively. Children of a migrant mother had a higher risk of both social-emotional problems and competence delay if they had a migrant father. The results highlight psychosocial health disparities in 2-year-old children and the need for research into mechanisms underlying these associations.